2013
DOI: 10.1179/2045772313y.0000000167
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship between wheelchair exercise capacity and life satisfaction in patients with spinal cord injury: A cohort study in the Netherlands

Abstract: Of 225 persons included, 130 attended two or more peak exercise tests, who were include in the analyses. Mean age at start was 39 years, 75% were male, 73% had paraplegia, and 76% had a traumatic lesion. Mean POpeak increased during the study from 32.9 to 55.9 Watts, mean VO2peak from 1.02 to 1.38 l/minute, and mean life satisfaction from 5.7 to 7.8. An increase of POpeak with 10 W was associated with a 0.3-point increase of life satisfaction (P = 0.01). An increase of VO2peak with 0.1 l/minute was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 43 publications
3
25
0
1
Order By: Relevance
“…The benefits include but are not limited to increased self-esteem [37], strength and endurance [38], social integration [39], physical independence [40] and life satisfaction [41]. In fact, the advantages of sport participation are so varied and impactful that these findings, along with overwhelming anecdotal evidence, assisted in the professional development of the field of therapeutic recreation [42].…”
Section: Impact Of Sports On Disabled Populationmentioning
confidence: 99%
“…The benefits include but are not limited to increased self-esteem [37], strength and endurance [38], social integration [39], physical independence [40] and life satisfaction [41]. In fact, the advantages of sport participation are so varied and impactful that these findings, along with overwhelming anecdotal evidence, assisted in the professional development of the field of therapeutic recreation [42].…”
Section: Impact Of Sports On Disabled Populationmentioning
confidence: 99%
“…Systematic monitoring of wheelchair-specific fitness after inpatient rehabilitation could be part of such a model, since it can support the maintenance of fitness (1). Maintaining wheelchair-specific fitness in people with long-term ScI can help to support health, participation in society and quality of life (3)(4)(5)9). Monitoring can also help to target those in most need of interventions; this need may differ between inactive people with long-term ScI, as indicated by the high variance in fitness in our study.…”
Section: Implications and Limitationsmentioning
confidence: 93%
“…the mean POpeaks in the subgroups with paraplegia (51 W) and tetraplegia (19 W) were approximately 30% lower than the mean POpeak determined in a systematic review of studies on fitness of people with paraplegia (74 W) and tetraplegia (26 W) (12). Such low POpeak values are alarming, as POpeak has been negatively associated with strain during Adl, health, participation and even quality of life (3)(4)(5)32). Furthermore, mean POpeak in our study (41 W) was approximately equal to that of a group of people at the start of inpatient ScI rehabilitation (35 W) (28).…”
Section: Vo2peak (L/min)mentioning
confidence: 93%
See 1 more Smart Citation
“…Aerobic capacity is an indirect measure of cardiovascular disease risk (Kohl 2001), and it has been suggested that low aerobic fitness increases the risk for cardiovascular disease after SCI (Hoffman 1986;Cowan et al 2010;de Groot et al 2013). Further, low aerobic fitness is associated with the inability to perform activities of daily living, increased frequency of urinary tract infections, and lower life satisfaction among individuals with SCI (Hjeltnes et al 1990;van Koppenhagen et al 2014). Conversely, peak aerobic capacity (VO 2 peak) is considered to be an excellent measure of both fitness and overall health in the able-bodied population (Aspenes et al 2011), and is associated with functional ability after SCI (Dallmeijer et al 2001).…”
Section: Introductionmentioning
confidence: 99%